2007
DOI: 10.1590/s0100-879x2006005000084
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 mediates the inhibitory effect of interleukin-6 on the proliferation of a hepatocarcinoma cell line in a STAT3-dependent manner

Abstract: The tissue inhibitor of metalloproteinases (TIMP)-1 is a multifunctional protein which is not only an inhibitor of matrix metalloproteinases (MMPs) but also to have a possible "cytokine-like" action. Here, we first compared mRNA expression of TIMP-1 and MMP-9 in BEL-7402 (a hepatocellular carcinoma cell line), L-02 (a normal liver cell line) and QSG-7701 (a cell line derived from peripheral tissue of liver carcinoma) using real-time quantitative RT-PCR. By evaluating the variation of the MMP-9/TIMP-1 ratio as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…These changes in MMPs expression and activity were similar to the molecular events involved in the pathogenesis of chronic rhino-sinusitis without nasal polyps, which involves high levels of IL-6 and IL-8 that trigger fibrosis by up-regulating TIMP-1 in fibroblasts [55]. In addition, the stimulation of TIMP-1 protein expression by IL-6, which was suggested in the present study, has also been reported in rat hepatocytes [56] and was indicated as a mechanism of cell growth inhibition [57], although a protective role of IL-6 associated with the induction of TIMP-1 was noted in hyperoxic acute lung injury [58].…”
supporting
confidence: 82%
“…These changes in MMPs expression and activity were similar to the molecular events involved in the pathogenesis of chronic rhino-sinusitis without nasal polyps, which involves high levels of IL-6 and IL-8 that trigger fibrosis by up-regulating TIMP-1 in fibroblasts [55]. In addition, the stimulation of TIMP-1 protein expression by IL-6, which was suggested in the present study, has also been reported in rat hepatocytes [56] and was indicated as a mechanism of cell growth inhibition [57], although a protective role of IL-6 associated with the induction of TIMP-1 was noted in hyperoxic acute lung injury [58].…”
supporting
confidence: 82%
“…This may also explain why ROS generation was not seen in HepG2 cells in the present study but was reported in L-02 hepatocytes. 40 Although both these cell lines are of human origin, the former is cancerous (HepG2), while the latter is not (L-02), 43 thereby possessing different genotypic and phenotypic features. Furthermore, it is well established that HepG2 cells do not possess the metabolic capacity of their innate in vivo counterparts, 44 which may also explain the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This latter line was derived from liver carcinoma peripheral tissue taken from a 35-year-old woman [50] and has been used in recent years for HCC studies [28,51,52]. Cells were grown in Dulbecco's modified Eagle medium (DMEM, Invitrogen) supplemented with 10% (v/v) heat-inactivated fetal bovine serum, 2 mM glutamine, 100 U/ml penicillin and 0.1 µg/ml streptomycin at 37 °C in an atmosphere of 5% CO 2 .…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%